Investigation on influencing factors and demand of remote hospice care willingness of tumor patients in Nanning City - LIU, Weichen; LI, Ming; LIAN, Siqin; HOU, Xijie; LING, Ying (Chinese Journal of Integrative Nursing, 2023)
Objective To explore the attitude and influencing factors of tumor patients towards remote hospice care in Nanning, so as to provide reference for improving the utilization rate of remote hospice care service. Methods A total of 148 patients with advanced cancer who were hospitalized in a tertiary hospital in Nanning from October 2021 to March 2022 were investigated with a self-made questionnaire on the demand for remote hospice care. Univariate analysis and binary logistic regression analysis were used to study the influencing factors of remote hospice care demand of advanced tumor patients. Results Totally 61 (41. 22%) tumor patients supported remote hospice care. Univariate analysis showed that age, education, family income, type of medical insurance, self-care ability and possession of smartphone were the main factors influencing their attitude (P<0. 05). Binary logistic regression analysis showed that age, monthly family income and type of medical insurance were the main factors affecting their attitude (P<0. 05). The 5 most in-demand services were pain control(83. 61%), nutritional counseling(78. 69%), nursing guidance(77. 05%), symptom control(73. 77%) and drug prescriptions(72. 13%). Conclusion Age, family income and type of health insurance are the main influencing factors for cancer patients to choose remote hospice care. Tumor patients have low awareness and moderate acceptance of remote hospice care, and have a greater demand for pain control, nutritional guidance and care guidance. (目的 探讨南宁市肿瘤患者对远程安宁疗护的态度及影响因素, 为提升远程安宁疗护服务利用率提供参考。方法 采用目的抽样方法, 选取2021年10月—2022年3月在南宁市某三级甲等医院住院的148例晚期肿瘤患者为研究对象, 采用自制的远程安宁疗护需求问卷对其进行调查, 采用单因素分析及二元Logistic回归分析研究晚期肿瘤患者远程安宁疗护服务需求的影响因素。结果 41. 22%(61/148)肿瘤患者对远程安宁疗护持支持态度。单因素分析显示年龄、学历、家庭收入、医保类型、自理能力、是否拥有智能手机等方面是影响其态度的主要因素(P＜0. 05)。二元logistic回归分析显示年龄、家庭月收入、医保类型是影响其态度的主要因素(P＜0. 05)。进一步分析服务需求, 排名前5位的依次是疼痛控制(83. 61%)、营养咨询(78. 69%)、照护指导(77. 05%)、症状控制(73. 77%)和药物处方(72. 13%)。结论 年龄、家庭收入及医保类型是肿瘤患者选择接受远程安宁疗护的主要影响因素。肿瘤患者对远程安宁疗护的认知程度低, 接受程度中等, 对疼痛控制、营养指导及照护指导的需求更大。)